THE EFFECTIVENESS OF ENGLISH COMIC IN TEACHING GRAMMAR (PRESENT AND PAST TENSE) - Rakhmawati, Dian (JURNAL SMART, 2018)
The goal of this study is to find out the effectiveness of English comic as media in teaching studentsâÂ  grammar. This study used One Group Pre-test and Post-testÂ  design. The result of the T-test computation showed that tobserved was higher than ttable (12.368>2.042), with the degree of freedom 30, the probability (Asymp.Sig.2 tailed) was lower than the level of significance (0.000<0.05). Based on the result, it can be concluded that there is significant difference between the pretest and posttest scores. It means that media of English Comic was used in teaching studentsâ grammar (simple present and past tense) is effective.Â Keywords: Effectiveness, English comic, studentsâ grammar